2014
DOI: 10.1097/cej.0b013e3283647453
|View full text |Cite
|
Sign up to set email alerts
|

Can serum angiogenin be used to improve the diagnostic performance in prostate cancer screening?

Abstract: Several biomarkers have been studied to avoid unnecessary biopsies resulting from suboptimal performance of prostate-specific antigen (PSA) testing. We aimed to assess the use of serum angiogenin as a prostate cancer diagnostic tool among candidates for biopsy. We selected 252 patients referred for ultrasound-guided transrectal prostate biopsy on the basis of an abnormal digital rectal examination and/or elevated total PSA. Serum angiogenin was quantitatively analyzed by solid-phase enzyme-linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Various malignant carcinomas, including prostatic cancer, depend on angiogenesis for growth, invasion, and progression. Pina et al [ 67 ] evaluated the serum levels of ANG as a diagnostic marker in the 252 patients who had prostate cancer. They noted that the median serum ANG levels were significantly higher in prostate cancer patients ( p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…Various malignant carcinomas, including prostatic cancer, depend on angiogenesis for growth, invasion, and progression. Pina et al [ 67 ] evaluated the serum levels of ANG as a diagnostic marker in the 252 patients who had prostate cancer. They noted that the median serum ANG levels were significantly higher in prostate cancer patients ( p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…1 ). In prostate cancer, hRNase5/ANG was also identified as an oncogene, as shown by its role in angiogenesis, a molecular target for the treatment, and a potential diagnostic biomarker [ 73 75 ]. Moreover, hRNase5/ANG plays a role in epithelial-mesenchymal transition (EMT) in squamous cell lung carcinoma to promote cell proliferation, migration, and invasion capacity through direct upregulation of a non-histone chromosomal high-mobility group protein [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…High serum levels of angiogenin were observed in patients with divergent cancers, including pancreatic cancer [39], colorectal cancer [37], bladder carcinoma [48], melanoma [49], B non-Hodgkin lymphoma [50], and prostate cancer [51], but to our knowledge, no previous studies addressed this issue in breast cancer. We demonstrated that serum ANG level of breast cancer patients was significantly higher than that of healthy donors.…”
Section: Discussionmentioning
confidence: 96%